Evolution, distribution, and characteristics of rifting in southern Ethiopia. Issue 4 (15th April 2014) - Philippon, Melody; Corti, Giacomo; Sani, Federico; Bonini, Marco; Balestrieri, Maria‐Laura; Molin, Paola; Willingshofer, Ernst; Sokoutis, Dimitrios; Cloetingh, Sierd
Abstract Southern Ethiopia is a key region to understand the evolution of the East African rift system, since it is the area of interaction between the main Ethiopian rift (MER) and the Kenyan rift. However, geological data constraining rift evolution in this remote area are still relatively sparse. In this study the timing, distribution, and style of rifting in southern Ethiopia are constrained by new structural, geochronological, and geomorphological data. The border faults in the area are roughly parallel to preexisting basement fabrics and are progressively more oblique with respect to the regional Nubia–Somalia motion proceeding southward. Kinematic indicators along these faults are mainly dip slip, pointing to a progressive rotation of the computed direction of extension toward the south. Radiocarbon data indicate post 30 ka faulting at both western and eastern margins of the MER with limited axial deformation. Similarly, geomorphological data suggest recent fault activity along the western margins of the basins composing the Gofa Province and in the Chew Bahir basin. This supports that interaction between the MER and the Kenyan rift in southern Ethiopia occurs in a 200 km wide zone of ongoing deformation. Fault‐related exhumation at ~10–12 Ma in the Gofa Province, as constrained by new apatite fission track data, occurred later than the ~20 Ma basement exhumation of the Chew Bahir basin, thus pointing to a northward propagation of the Kenyan rift‐related extension in the area.